Design, Kinematic Analysis, and Scaled Prototype Validation of a Pneumatic Ejection Mechanism for Supersonic Re-Entry Capsule Testing - Ahmad Samsul Arbai; Azzahra Nazwa Asyifa; Rajni Rizkia Sirat; Johnson Fernando; Rahmat Dani Sulistyo; Fajrul Falah (Multidisciplinary Innovations and Research in Applied Engineering, 2026)
Lunar rover wheels must combine low mass, traction, compliance, abrasion resistance, and maintainability under vacuum, thermal cycling, and unconsolidated regolith. This study develops and evaluates an adaptive traction rover wheel for lunar surface mobility applications. The method combined requirement definition, terramechanics-based grouser sizing, material selection, CAD-based structural packaging, finite element evaluation, manufacturability assessment, and service-life estimation. The proposed wheel uses a two-piece Ti-6Al-4V rim, ten alternating compliant titanium spokes, ten 27 mm V-shaped grousers, a 6061-T6 aluminum hub, riveted mechanical joints, and Cr3C2-NiCr HVOF coating on soil-contact surfaces. The design achieved a diameter of 0.457 m, a width of 0.203 m, and a total mass of 2.254 kg. Linear-elastic structural screening indicated that the wheel supported a nominal normal load of 256 N with a factor of safety of approximately 2 based on a minimum Ti-6Al-4V yield-strength criterion of 828 MPa. The 3 g impact screening case produced a local peak von Mises stress of approximately 900 MPa, exceeding this conservative yield criterion and therefore requiring nonlinear analysis and experimental validation. Traction capability, wear resistance, and 1,000 km service-life estimates are analytical projections derived from geometry and wear modeling, not fully validated operational performance. The proposed architecture is therefore a lightweight, repairable, and traction-oriented wheel concept requiring targeted laboratory validation before mission use.